2018
DOI: 10.1016/j.bja.2017.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RhoA reduces propofol-mediated growth cone collapse, axonal transport impairment, loss of synaptic connectivity, and behavioural deficits

Abstract: Inhibition of RhoA prevents propofol-mediated hippocampal neurotoxicity and associated cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 116 publications
(92 reference statements)
4
39
0
Order By: Relevance
“…these young neurones during this specific critical period of development that is interrupted and later manifests as behavioural impairment. This hypothesis is further supported by findings recently showing that maintaining synapses, 17 rather than preventing cell death, 16 protects from cognitive impairment. Our results, showing a difference in cognitive outcome in females at P4 vs P7 and a difference in the expression of chloride transporters, lend additional evidence to this argument.…”
Section: Discussionsupporting
confidence: 64%
“…these young neurones during this specific critical period of development that is interrupted and later manifests as behavioural impairment. This hypothesis is further supported by findings recently showing that maintaining synapses, 17 rather than preventing cell death, 16 protects from cognitive impairment. Our results, showing a difference in cognitive outcome in females at P4 vs P7 and a difference in the expression of chloride transporters, lend additional evidence to this argument.…”
Section: Discussionsupporting
confidence: 64%
“…Under normal cellular conditions, retrograde transport occurs when neurotrophins bind to plasmalemmal NTRs (TrkA, TrkB) followed by endocytosis and attachment to microtubules to facilitate intracellular transport down the axon. Evidence shows that impaired retrograde axonal transport occurs in many neurodegenerative conditions, such as Alzheimer disease, Parkinson disease, ALS, and anesthetic neurotoxicity (39)(40)(41)(42)(43). Neurotrophin/Trk signaling, growth cone motility, and synaptic modulation is dependent on MLRs (9,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Over polymerized actin are found to be associated with neural degeneration and cognitive dysfunction [16]. Previous studies have reported the reorganization of actin induced by propofol [6]. In one of our early research, we found increased F-actin level in old rat hippocampus after propofol anesthesia, which was closely related to the depression of LTP, indicating the important roles of overpolymerization of actin in synaptic dysfunction after propofol anesthesia [8].…”
Section: Discussionmentioning
confidence: 62%
“…For example, propofol has been reported to inhibit LTP [5]. It was also found to be able to modulate actin dynamics [6]. How about the status of actin dynamic after anesthesia?…”
Section: Introductionmentioning
confidence: 99%